NEW URBAN AGENDA AND THE ISLAND BASED SETTLEMENTS DEVELOPMENT - Johan Silas (Journal of Architecture&ENVIRONMENT, 2016)
World population entered the first two decades of the XXI Century did not meet the grand expectation of a prosperous and just world as poverty and all it’s consequences are still widely visible in fast growing cities. As the more people are now living in urban areas, in towns and cities, obviously their future depend on the social justice, healthy economic growth and quality environment. In the Habitat III meeting in Quito Ecuador (10-2016), they endorsed and agreed on a new agenda for meeting the challenges faced by the world in term of (urban) place where people can actualised themselves in meeting the new opportunities and changes offered in the course of time. The result of this research is that Indonesia needs to further adopt and adapt the New Urban Agenda  to meet the unique need and situation of Indonesia in the future which  can only be done by native experts (Indonesia) as experience and interest should rest on the shoulder of Indonesian.